Relationship between Incentive and Posyandu Cadre Performance in Increasing Visits to Children to Posyandu in the Work Area of the Public Health Center in North Buton Regency - Ashan, La Ode; Saafi, La Ode; Tasnim, Tasnim; Amraeni, Yunita (Magister Kesehatan Universitas Mandala Waluya, 2022)
Introduction: Incentives really need to be given to Integrated Healthcare Center cadres, providing incentives for Integrated Healthcare Center cadres in the working areas of the Waode Buri and Kulisusu Health Centers based on the North Buton Regent's Regulation on Procedures for Providing Incentives and Strengthening the Capacity of Integrated Healthcare Center Cadres. Thus, researchers need to research the relationship between incentives and the performance of Integrated Healthcare Center cadres to increase the visits of children under five to the Integrated Healthcare Center. Method: This type of research is quantitative with a cross-sectional study approach. The population of all Integrated Healthcare Center cadres is 110 people with a sample of 87 respondents, the sample is drawn using simple random sampling. Result: The chi square statistical test at the 95% confidence level (α = 0.05) shows that the p value = 0.000 because Ho is rejected or Ha is accepted which means there is a relationship between incentives and the performance of Integrated Healthcare Center cadres, with a value ofj=0.513 indicates a strong relationship. Conclusion: There is a significant relationship between incentives and the performance of Integrated Healthcare Center cadres in increasing visits for toddlers to the Integrated Healthcare Center in the working area of ​​the Waode Buri Health Center and the Kulisusu Health Center, North Buton Regency.